Diagnosis of Deep Infiltrating Endometriosis Using Transvaginal Ultrasonography - Yin, Shaoli; Lin, Qi; Xu, Fanhua; Xu, Jinfeng; Zhang, Yujuan (Frontiers in Medicine, 2020)
[Abstract] Objective To investigate the diagnostic value of transvaginal ultrasonography in different location involved by deep infiltrating endometriosis. Methods women suggestive of DIE were included in the study from January 2017 to December 2019 in our hospital,and routine transvaginal sonography examinations were performed by an experienced doctor before surgery. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of ultrasound in diagnosis of involved targets were calculated compared with surgery and pathology findings. The ultrasonographic features of involvement lesions were summarized. Results There were 198 patients confirmed as DIE by operation and pathology, including 170 cases of uterosacral ligament involvement, se: 96.47% ,sp: 85.71%; 79 cases of intestinal involvement, se: 94.94% and sp: 94.96%; 57 cases of vaginal rectal septum lesions, se: 73.68% and sp: 94.33%; vaginal 20 cases, se： 50% and sp: 97.21%; 3 cases of bladder, se: 66.7% and sp: 100% ;9 cases of ureter, se: 55.56% and sp:100%; 10 cases of broad ligament involvement, se:10% and sp: 100%. Conclusion Transvaginal ultrasonography plays an important role in diagnosing DIE by using some methods to avoid the interference factors.